Artes marciales bajo el bloqueo de COVID-19: la pragmática de la pedagogía creativa - Jennings, G. (Sociología del Deporte, 2020)
Martial arts organisations increasingly blend online and offline activity in order to cultivate specific qualities, skills and virtues. Students and instruc-tors use blogs, chat fora, videos and podcasts to supplement their self- and shared cultivation, and this expanded with the COVID-19 lockdown in Britain. Martial arts schools have been closed and even disbanded while governments control people`s physical interactions through social distancing measures. This article draws on case studies of two British martial arts schools (Taijiquan and historical fencing) in order to examine how they have adapted to the lockdown. It offers these case studies to narrate the developments of how teachers and their localised communities have been creative during this moment of international crisis - from instructor-led online, live training sessions and lectures to student-led chat fora and movie nights for continued sociability and identity construction. In so doing, this article makes use of martial arts theories: Shared Cultivation (Jennings, 2010) and Martial Creation (Jennings, 2019) to explain how martial artists continue to develop through creative online endeavours and through their moving bodies within the confines of their homes. Finally, I argue that this creative martial arts cultivation during the COVID-19 pandemic might be extended to wider physical culture.